Integration of Validity, Reliability, Trustworthiness, and Authenticity Concepts in Maintaining the Quality of Scientific Research - Yanti, Herina; Dwi, Gebi Sintia; Putri, Vebionita Megi; Zulfani, Zulfani (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
This study aims to integrate the concepts of validity, reliability, trustworthiness, and authenticity in maintaining the quality of scientific research in both quantitative and qualitative approaches. These four concepts play a crucial role in ensuring the accuracy, consistency, credibility, and originality of research findings. This study employs a library research method by analyzing various literatures related to research methodology. The results show that validity and reliability are fundamental in quantitative research to guarantee the precision and consistency of instruments, while trustworthiness and authenticity are essential in qualitative research to assess credibility, transferability, dependability, confirmability, and the authenticity of participants’ experiences. The integration of these four concepts can be achieved through a mixed-methods approach that combines empirical strength with reflective depth to enhance both the accuracy and the honesty of data representation. In conclusion, validity, reliability, trustworthiness, and authenticity should not merely be seen as technical procedures but as ethical foundations to ensure the integrity and credibility of scientific research.